Insects as an alternative protein source for poultry nutrition: a review - Belhadj Slimen, Imen; Yerou, Houari; Ben Larbi, Manel; M’Hamdi, Naceur; Najar, Taha (Frontiers in Veterinary Science, 2023)
This review summarizes the most relevant scientific literature related to the use of insects as alternative protein sources in poultry diets. The Black soldier fly, the housefly, the beetle, mealworms, silkworms, earthworms, crickets, and grasshoppers are in the spotlight because they were identified as an important future source of sustainable animal proteins for poultry feeding. Insect meals meet poultry requirements in terms of nutritional value, essential amino acid composition, nutrient digestibility, and feed acceptance. Furthermore, they are enriched with antimicrobial peptides and bioactive molecules that can improve global health. Results from poultry studies suggest equivalent or enhanced growth performances and quality of end-products as compared to fish meal and soybean meal.To outline this body of knowledge, this paper states established threads of research about the nutrient profiles and the digestibility of insect meals, their subsequent effects on the growth and laying performances of poultry as well as the quality of meat, carcass, and eggs. To fully exploit insect-derived products, the effects of insect bioactive molecules (antimicrobial peptides, fatty acids, and polysaccharides) were addressed. Furthermore, as edible insects are likely to take a meaningful position in the feed and food chain, the safety of their derived products needs to be ensured. Some insights into the current knowledge on the prevalence of pathogens and contaminants in edible insects were highlighted. Finally, the effect of insect farming and processing treatment on the nutritive value of insect larvae was discussed. This is a provisional file, not the final typeset article Our overview reveals that using insects can potentially solve problems related to reliance on other food sources, without altering the growth performances and the quality of meat and eggs.